Effect of Cholecystectomy on the Occurrence of Knee Osteoarthritis - Zeng, Ling‐yuan (Orthop Surg, 2020)
OBJECTIVE: To evaluate the effect of cholecystectomy on the occurrence of knee osteoarthritis (KOA). METHODS: The present study was a case‐control study with a retrospective, cross‐sectional, and longitudinal study design. The clinical data for knee osteoarthritis in the Second Hospital of Shanxi Medical University from January 2016 to September 2018 was analyzed. Clinical data, including gender, age, height, weight, smoking, alcohol abuse, prior medical history, and previous surgical history, were recorded. A logistic regression model was used for the univariate and multivariate analysis. RESULTS: A total of 1659 patients with KOA (KOA group) and 1195 limb fracture patients (control group) were included in this study. Among the 1659 patients with KOA, 388 patients were male and 1271 were female, while among the 1195 patients in the control group, 638 patients were male and 557 patients were female. The period between cholecystectomy and knee osteoarthritis onset ranged from 0.5 years to 17 years; the average interval time was 8.73 ± 2.11 years. The age at disease onset was significantly older when compared to the control group, while the body mass index in the KOA group was significantly higher when compared to the control group (P < 0.05). There were 97 patients undergoing cholecystectomy in the KOA group and there were 15 patients undergoing cholecystectomy in the control group. The proportion of cholecystectomy in the two groups was statistically significant. After the univariate analysis, there was a statistically significant difference in distribution between the two groups (P < 0.05). The multivariate logistic regression analysis revealed that there was a significant difference in the distribution of these two groups (P < 0.05), indicating that cholecystectomy is associated with the occurrence of KOA. CONCLUSION: There is a close relationship between cholecystectomy and KOA. However, the specific mechanism remains unknown and should be further researched.